2021
DOI: 10.21203/rs.3.rs-690859/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Unmet Need for Family Planning Among Married Women in Zambia: Lessons from the 2018 Demographic and Health Survey

Abstract: Introduction: Unmet need for family planning among married women is still high in Africa. In the year 2018, one in every five married women in Zambia had an unmet need for family planning. Unmet need for family planning can increase the number of unintended pregnancies and abortions, both of which have the potential to increase the proportion of women of child bearing age who are at high risk of birth complications. Studies have shown that factors explaining unmet need for family planning vary significantly fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
8
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 6 publications
3
8
1
Order By: Relevance
“…Our analysis revealed that geographical residence (rural vs urban), age of woman, socioeconomic status, number of children ever born to a woman (parity), employment status and partner’s age constituted factors significantly associated with unmet need for family planning. These findings are largely consistent with other studies (22, 30-31) including a Zambian study which analysed unmet need for family planning using the 2018 DHS data (30). From a review of literature predictors of contraceptive uptake and unmet need for family planning are similar for HIV positive and HIV negative women.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Our analysis revealed that geographical residence (rural vs urban), age of woman, socioeconomic status, number of children ever born to a woman (parity), employment status and partner’s age constituted factors significantly associated with unmet need for family planning. These findings are largely consistent with other studies (22, 30-31) including a Zambian study which analysed unmet need for family planning using the 2018 DHS data (30). From a review of literature predictors of contraceptive uptake and unmet need for family planning are similar for HIV positive and HIV negative women.…”
Section: Discussionsupporting
confidence: 90%
“…Our study findings also suggest that the more children a woman has the higher the chances they have an unmet need for family planning. This is in line with study findings from Zambia (30) Ethiopia (45-46) and Kenya (47) including a multi-country study that analysed nineteen DHS survey data from Sub-Sahara Africa (48). It is probable that with higher parity, women will have attained the desired number of children hence a greater need for limiting and in the context of limited access to contraceptive services the unmet need is potentially high.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The prevalence rate of teenage pregnancy among adolescents aged 15-19 in Africa is 18.8% while that of sub-Saharan Africa (SSA) is around 19.3% [3]. The drivers of teenage pregnancy are several and multifaceted and these include poverty, inadequate education and employment opportunities, gender inequalities, rural residence, poor access and low use of contraceptives and inadequate sexual and reproductive health (SRH) information among others [3][4][5][6]. Marital status is another major factor associated with teenage pregnancies.…”
Section: Introductionmentioning
confidence: 99%